Dealing with Climate-Related Risks: Some Pioneering Ideas for Enhanced Pastoral Risk Management in Africa - Ouma, R.; Mude, Andrew G.; Steeg, Jeannette van de (Cambridge University Press, 2011)
This paper makes the case for innovative risk management approaches in pastoral settings, which may include adjustments to the traditionally practiced approaches that have become progressively less effective. We use recent data from studies in Kenya and southern Ethiopia to confirm that traditional pastoral risk management approaches are increasingly futile against increasing external pressures, seasonal rainfall variability and future climate change. Some pioneering approaches and ideas, with potentially wider application to African pastoral settings, appear to offer greater hope; these include pilot studies designed to demonstrate the efficacy of index-based risk transfer products in pastoral systems, improvements in the management of food insecurity response for pastoralists and the recasting of development interventions as risk management. The International Livestock Research Institute, in collaboration with a wide range of partners, is currently testing these ideas.